Endoscopic ultrasound‐guided gastrojejunostomy versus robotic gastrojejunostomy for unresectable malignant gastric outlet obstruction - Rishi Pawa; Nicholas J Koutlas; Greg Russell; Perry Shen; Swati Pawa (DEN Open, 2024)
Abstract Objectives Malignant gastric outlet obstruction (GOO) has traditionally been managed with enteral stenting and surgical gastrojejunostomy. Our study aimed to compare outcomes between endoscopic ultrasound‐guided gastrojejunostomy (EUS‐GJ) using a lumen‐apposing metal stent and robotic GJ (R‐GJ) for unresectable malignant GOO. Methods Patients undergoing EUS‐GJ or R‐GJ for unresectable malignant GOO were retrospectively analyzed. The primary outcome was clinical success defined by the ability to tolerate oral intake at the time of discharge. Secondary outcomes included technical success, procedure duration, adverse events, and post‐procedure length of stay (LOS). Results A total of 44 patients met the inclusion criteria. Of the 44, 29 underwent EUS‐GJ and 15 underwent R‐GJ. Age, gender, malignant etiology, and presence of ascites were similar between the two groups. Patients treated with EUS‐GJ had a higher mean Charlson comorbidity index (10.3 vs. 7.0; p ≤ 0.0001) and a lower preoperative body mass index (22.3 vs. 27.2; p = 0.007). Technical and clinical success was achieved in 100% of patients in both groups (p > 0.99). EUS‐GJ was associated with shorter procedure duration (57.5 vs. 146.3 min; p < 0.0001), hospital LOS (4.3 vs. 8.2 days, p = 0.0009), and time to oral intake (1.0 vs. 5.8 days; p < 0.0001) when compared to R‐GJ. Adverse events occurred in 5 of the R‐GJ patients and none of the EUS‐GJ patients (p = 0.003). Conclusions EUS‐GJ has similar efficacy and superior clinical outcomes compared to R‐GJ in the management of malignant GOO. Prospective studies with longer follow‐up duration are needed to validate these findings.